Reconstruction of a Large Defect of the Glabella - Miroux Catarino, Alexandre (2019)
The reconstruction of large defects of the glabella, especially when involving the forehead, is a surgical challenge. Surgical reconstruction of this location should take into account aesthetic subunits, avoid approximation of eyebrows and maintain symmetry of the face. The authors present a case with reconstruction of a surgical defect involving the glabella and the forehead after Mohs surgery. An A-T advancement flap to close the superior portion of the defect was combined with a rhomboidal transposition flap for closing the lower zone in order to maintain the distance between the eyebrows. Reconstruction by aesthetic subunits and the association of flaps allowed a good aesthetic and functional result.